Analysing an influence of initial bus route networks in competitive optimization of multiple bus companies - R. Zhou; N. Yatsu; I. Nakari; K. Takadama (SICE Journal of Control, Measurement, and System Integration, 2023)
This paper focuses on the bus route network optimization where two bus companies compete with each other to increase a convenience of passengers and profits of bus companies, and analyses how the optimized bus route networks are affected by their initial route networks. The intensive simulation of the competition of bus companies in the Mandl benchmark problem has revealed that (1) the similar initial route networks derive the highly competitive situation where the lines of either company dominate but the topology and characteristic (i.e. the number of edges) of the network of another company remain in the optimized network; (2) the different initial route networks derive the moderately competitive situation where the number of lines of the two companies become equal and the characteristic (i.e. the number of ring routes and edges) of the networks of two companies is averaged; and (3) the intermediately similar initial route networks do not only show the similar tendency of the similar initial route network but also derive a new feature of merging the topology and characteristic of the networks of two companies.